Computational fluid dynamic modelling of water-cooling mechanism during thermal spraying process. (21st August 2007) - Kamnis, Spyros; Gu, Sai
A Computational Fluid Dynamic (CFD) model is developed to examine the heat transfer process through the water-cooling mechanism in a High Velocity Oxygen Fuel (HVOF) thermal spraying system. The water-cooling configuration is composed of a series of discrete holes through the copper-made thermal spraying gun. Unstructured grid is employed for both liquid and solid regions and the water-cooling model is fully integrated with the gas flow dynamics where combustion, turbulent flow and free jet expansion are included. The numerical results indicate that the water flow direction has noticeable influence on the cooling efficiency due to the variation of heat capacity of water and the current cooling mechanism has no noticeable effect on the gas flow dynamics within the thermal spraying gun.